Analisis Kesesuaian Lokasi Supermarket Terhadap Pasar Tradisional Di Kecamatan Cihideung - Zakiah Darajat; Fadilla Kamal; Lintang Kedjora Silvanissa; Nirmansyah Nirmansyah; Dila Laila Ramadani; Pajar Sutrisna; Denina Denina; Handi Rajib Ghani; Setio Galih Marlyono (Geosfera: Jurnal Penelitian Geografi, 2025)
Cihideung Subdistrict is one of the centers of economic activity in Tasikmalaya City, which has shown rapid development in the field of trade. This area accommodates various forms of community economic activities, both traditional and modern. The rapid growth of contemporary retail has created new challenges in terms of economy and spatial planning, particularly in relation to the sustainability of conventional markets and the balance of urban space functions. This research methodology uses Geographic Information System (GIS)-based spatial analysis to evaluate the compliance of the distance between modern and traditional markets, in accordance with local regulations that stipulate a minimum distance of 1,000 meters. The analysis results show that four supermarkets in the study area are located within a 1,000-meter radius, thus violating the regulations established by the Mayor of Tasikmalaya Number 1 of 2015. This condition has a significant impact on the economy, society, environment, and urban spatial planning, including a decline in the income of traditional traders, changes in community consumption behavior, and an increase in vehicle volume that causes traffic congestion. However, in addition to these negative impacts, this situation also has positive effects, such as the creation of formal sector jobs and improved job skills for young people. Furthermore, bargaining activities in traditional markets tend to decrease